2017
DOI: 10.24925/turjaf.v5i10.1125-1129.991
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Honey Sourced from Natural and Artificial Apiaries in Ekiti State, Nigeria.

Abstract: Honey samples were obtained from wild and domesticated sources and analyzed for some physicochemical properties such as color, pH, moisture content, ash content, refractive index, specific gravity, total solid, viscosity, glucose and fructose content following Standard Association of Official Analytical Chemistry. The following range of values for pH (3.55-4.20), moisture content (18.50-25.60%), soluble solids (74.10-81.20%), ash content (0.08-0.14%), specific gravity (1.38-1.47), refractive index (81.3-83.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Calcium levels were only measured in BBIA Bogor, and the highest of 270 mg/kg was found in Bengkalis honey. The calcium level in this study was higher than that in honey from natural hives in Nigeria that ranges between 37,76 and 40,90 mg/kg (35) and honey from Tunisia that ranges between 221,07 and 113,85 mg/kg honey (13).…”
Section: Changes In Riau Honey Composition After Inter-island Shippingcontrasting
confidence: 68%
See 1 more Smart Citation
“…Calcium levels were only measured in BBIA Bogor, and the highest of 270 mg/kg was found in Bengkalis honey. The calcium level in this study was higher than that in honey from natural hives in Nigeria that ranges between 37,76 and 40,90 mg/kg (35) and honey from Tunisia that ranges between 221,07 and 113,85 mg/kg honey (13).…”
Section: Changes In Riau Honey Composition After Inter-island Shippingcontrasting
confidence: 68%
“…The predominant minerals in honey are potassium, sodium, calcium, and magnesium (14). The mineral content of honey is manifested in its color, that is, dark honey has more minerals than light honey (35). Consumption of honey provides calcium that is easily absorbed and could strengthen bone mass.…”
Section: Changes In Riau Honey Composition After Inter-island Shippingmentioning
confidence: 99%
“…In comparison with refined sugar, honey reduce weight gain and adiposity, presumably due to lower food intake and also promote lower serum triglycerides [20]. There is need to assess the effect of natural honey on the blood glucose and serum iron levels of non-diabetic rats [21,22]. Hence, this study was carried out to determine the effect of natural honey and refined granulated sugar on blood glucose and serum iron level on albino rats in Awka, Anambra State.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the quality assessment of natural honey produced in Nigeria [4,5,1,2]. Ndife et al [2] investigated the comparative quality of honey obtained from different floral in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that there is variability in some quality characteristics of honey samples from different regions of Nigeria, and that those from the northern region had the best overall acceptability ratings. Oyeyemi [5] studied the quality assessment of honey sourced from natural and artificial apiaries in Ekiti State, Nigeria. He found that honey from artificial and natural apiaries is of good quality in terms of some important physicochemical parameters (pH, ash, glucose, fructose contents, glucose/ fructose ratio) which were within the international standard limit.…”
Section: Introductionmentioning
confidence: 99%